Propulsion in elite low-point classification rugby wheelchair athletes - Haydon, D. S.; Pindoer, R. A.; Grimshawa, P.; Robertson, W. S. P. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
Wheelchair propulsion kinematics have been demonstrated to be dependent on chair configuration, although this knowledge is still limited in wheelchair rugby. This study monitored the propulsion kinematics during sprint performance in elite low-point wheelchair rugby athletes, with correlations between kinematics, athlete experience and configuration investigated. Increased experience was correlated with decreasing contact and push angles for the second push, as well as trends for the first and third pushes. Configuration parameters such as seat depth, seat angle, and seat depth-to-thigh length, were also shown to be correlated with kinematic variables. Findings provide important information for the configuration of wheelchairs to utilise efficient regions of their stroke and optimise sprint performance.